Hubungan Lama Penggunaan Kontrasepsi Pil Kombinasi Dengan Kejadian Hipertensi Di Wilayah Puskesmas Sumbersari Kabupaten Jember - Elvina, Hilda Yuni; Kiswati, Kiswati; Restanty, Dian Aby (Jember Maternal and Child Health Journal, 2024)
Hormonal disruptions brought on by long-term usage of combined pill contraceptives can have an effect on blood pressure. Serious consequences can arise from untreated hypertension, also known as high blood pressure. According to the 2018 Riskesdas, hypertension affected 51.17 percent of women and 48.83 percent of males. With 3,934 participants, the Sumbersari Health Center had the greatest number of people who accepted combination tablet contraceptives in a preliminary trial. In the Sumbersari Health Center region of Jember Regency, researchers set out to find out how often hypertension is and how long people have been taking combination pill contraceptives. A cross-sectional design was employed in this investigation. Out of a total population of 271 women, 55 were selected using the Simple Random Sampling approach. Questionnaires, KB cards, and a Taff Omicron B869/BW3205 Digital Tensimeter with Chi-Square Test analysis were the research measuring instruments. Hypertension is not experienced by the majority of users of new category combination pill contraceptives (<2 years) (29%), and only a tiny percentage of users (16.3%) do experience hypertension. The majority of people who have used old-category combination pill contraceptives for at least two years (54.6% of the total) have hypertension, while a tiny percentage of those people (11%) do not. The correlation between the duration of using combination pill contraceptives and the occurrence of hypertension was confirmed by the chi-square test, which yielded a p-value of 0.002 <? 0.05. Most users of old category combination pill contraceptives (?2 years) experienced hypertension (54.6%). So that acceptors of combination pills are expected to replace other contraceptives if they have used combination pills for ?2 years and experience symptoms of hypertension.